PENGARUH LATIHAN PASSING BAWAH DENGAN DINDING SEKOLAH TERHADAP KEMAMPUAN PASSING BAWAH BOLA VOLI SISWA EKSTRAKURIKULER SMP NEGERI 3 PELEPAT - Putra, Ikhsan Maulana; Saleh, Khairul; Hamzah, Iri; Zunarti, Rita; Apdoludin, Apdoludin; aprlia, assayya datina (Jurnal Muara Olahraga, 2023)
The problem in this study is that students have not been able to pass down correctly, the accuracy of the arms in passing down the students is still lacking, both knees of the students are not bent so that the passing is not calm. This study aims to determine the effect of lower passing training with the school wall on the ability of lower passing volleyball extracurricular SMP Negeri 3 Pelepat. This research is a quantitative experimental study, the method used in this study is an experiment in the form of a one group pre-test post-test design. The population in this study was 55 people. The sampling technique used purposive sampling with a sample size of 15 students. Data collection techniques using tests. The instrument used was the lower passing test and the data analysis technique used the paired sample t-test with the help of the SPSS version 26 application. The results showed that there was an effect of lower passing training through the use of school walls on the lower passing of volleyball extracurricular SMP Negeri 3 Pelepat. Evidenced by data analysis using the t test, the results of this study show the value of tcount (11.611) > ttable (2.144), and the p value (0.000) < from 0.05, then Ha: accepted and Ho: rejected. The conclusion of this study is that there is an effect of lower passing training through the use of school walls on the lower passing of volleyball extracurricular SMP Negeri 3 Pelepat.